A Combined Health Action Process Approach and mHealth Intervention to Increase Non‐Sedentary Behaviours in Office‐Working Adults—A Randomised Controlled Trial. Issue 3 (28th April 2020) - Rollo, Scott; Prapavessis, Harry
Abstract : Background: Office‐working adults represent an at‐risk population for high levels of sedentary behaviour (SB), which has been associated with an increased risk for numerous chronic diseases. This study examined the effectiveness of a Health Action Process Approach (HAPA) based planning intervention augmented with tailored text messages to reduce workplace sitting time (primary outcome) and increase specific non‐SBs (i.e. standing time, walking time, stretching time, break frequency, break duration). A secondary purpose was to examine relationships among HAPA volitional constructs and sedentary and non‐SBs. Methods: Full‐time office workers ( M age  = 45.18 ± 11.33 years) from Canada were randomised into either a HAPA intervention ( n  = 29) or control ( n  = 31) condition. Workplace sitting time, time spent in specific non‐SBs, and HAPA volitional constructs were assessed at baseline, weeks 2, 4, 6 (post‐intervention), and 8 (follow‐up). Results: Significant group by time interaction effects, that favoured the intervention group, were found for sitting time ( p  = .003, ɳp 2  = .07), standing time ( p  = .019, ɳp 2  = .05), and stretching time ( p  = .001, ɳp 2  = .08) as well as for action planning ( p  < .001, ɳp 2  = .20), coping planning ( p  < .001, ɳp 2  = .18), and action control ( p  < .001, ɳp 2  = .15). Significant correlations ( p  < .05) were also found between the HAPA constructs and time spent sitting, standing, walking, as well as break frequency. Conclusions: Augmenting a HAPA‐based planning intervention with text messages can reduce workplace sitting time in office workers. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT03461926.